Substituent effects in pyridyl-functionalized pyrylium salts, pyridines and λ3, σ2-phosphinines: a fundamental and systematic study. Issue 28 (28th June 2018) - Loibl, Antonia; Oschmann, Wiebke; Vogler, Maria; Pidko, Evgeny A.; Weber, Manuela; Wiecko, Jelena; Müller, Christian
Abstract : A series of pyridyl-functionalized O + –, N–, and P– containing heterocycles have been prepared and investigated for substituent effects. Abstract : A series of substituted, pyridyl-functionalized 2, 4, 6-triarylpyrylium salts were prepared and investigated for their light absorption and emission properties. After reaction with P(SiMe3 )3, the corresponding λ 3 -phosphinines were obtained, which carry on the 4- or 6-aryl ring ±I and ±M substituents. Supported by DFT calculations, a systematic evaluation of the σ-donor and π-donor as well as π-acceptor properties of these low-coordinate P, N-hybrid ligands was performed. The modular synthetic approach allowed us at the same time to synthesize the structurally related bipyridine derivatives for comparison reasons. Reaction of the chelating ligands with [W(CO)6 ] in THF afforded the corresponding [(P^N)W(CO)4 ] and [(N^N)W(CO)4 ] complexes. A crystallographic characterization of selected coordination compounds revealed significant structural differences between the pyridyl-phosphinine- and the bipyridine-based compounds. Their characterization by means of IR-spectroscopy gave experimental insight into the electronic properties of the respective ligands.